The behavioural economist and the social planner: To whom should behavioural welfare economics be addressed? - Robert Sugden (Max Planck Institute of Economics, 2011)
This working paper is a lightly edited version of two chapters of a book that I am currently writing. This book will present and defend a form of normative economics that conserves the main insights of the liberal tradition of classical and neoclassical economics but does not depend on strong and implausible assumptions about individual rationality. In this paper, I ask who the addressee of normative economics should be. Conventional welfare economics, both neoclassical and behavioural, asks what is good for society from an impartial perspective - the view from nowhere. Explicitly or implicitly, its recommendations are addressed to an imagined benevolent despot. I argue for an alternative, contractarian approach, in which recommendations are addressed to individuals who are looking for ways of coordinating their behaviour to achieve mutual benefit. The contractarian approach disallows paternalistic recommendations, since these have no valid addressee.
Keywords: 330; Wohlfahrtstheorie; Normative Ökonomik; Verhaltensökonomik; Sozialvertrag; Verfassungsökonomik; Theorie